Pendampingan Aplikasi e-Plantasia untuk Meningkatkan Literasi Pembelajaran Botani berbasis Digital bagi Pustakawan Di Kabupaten Magetan - Hani Atun Mumtahana; Ani Sulistyarsih; R.Bekti Kiswardianta; Wachidatul Linda Yuhanna (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Digital transformation is driving changes in literacy skills and technology-based information services. The Regional Archives and Library Service (ARPUS) of Magetan Regency is one government agency that has utilized technology and information in conducting business processes. The use of information technology is also implemented in several libraries within the region. This requires ARPUS to introduce digital media-based innovations in its services. One such effort is utilizing a learning platform to provide digital literacy-based learning resources. This activity is in the form of Community Service (PkM) which is carried out by mentoring librarians to utilize the e-plantasia platform as a botany learning medium. This activity is carried out using a participatory mentoring method based on training and direct practice (hands-on training) which includes needs analysis, training, practice, and evaluation through pre-test and post-test. The results show that participants have a sufficient initial understanding of digital literacy, but do not yet fully understand the use of the e-Plantasia application. After the training, there was an increase in the average post-test score on all indicators, from the range of 60–70 to 80–86, as well as an increase in readiness for implementation in library services. Thus, mentoring activities have proven effective in improving librarians' competence in utilizing digital media as an innovation in library literacy services.